The Weaponising of Freedom of Speech: Theological Ethics in the Academy? - McIntosh, Esther ca. 20./21. Jh. (Studies in Christian ethics, 2026)
In the UK (and the US as well as elsewhere) freedom of speech is being weaponised in the academy in ways that effectively curtail those who speak to truth to power and who challenge colonialist behaviour and related injustice. This article examines the direction of travel in UK academia in recent years related to both freedom and ethics through two key movements: trans rights and Palestine solidarity. Particular attention is given to definitions of academic freedom and freedom of speech, related government policy and its effects, and the moral duties of theologians and theological ethicists. In conclusion, the article calls for a new theological ethics that can stand up against injustice and the increasingly authoritarian moves of governments and university managers.